Transceiver design and performance analysis for uplink SCMA based on CP-free OFDM - Li ZHOU; Xiqing LIU (Dianxin kexue, 2021)
A typical sparse code multiple access (SCMA) system utilizes orthogonal frequency division multiplexing (OFDM) technology with cyclic prefix (CP) to combat multipath fading in wireless channels.Therefore, its capacity is reduced by the CP-insertion.To address this issue, the SCMA scheme based on CP-free OFDM using the time domain precoding (TDP) algorithm was proposed and the proposed scheme was termed as TDP-OFDM SCMA.The transceiver structure was designed, and the capacity plus the bit error rate (BER) performances under various channels with different overload rates and with channel estimation errors were evaluated via the simulations.Also, the power consumption problem in TDP-OFDM SCMA was discussed.The simulation results show that under the same overload rate, the capacity of TDP-OFDM SCMA can be increased by up to 25% if compared with the SCMA based on CP-OFDM.